The Effect Of Covid-19 On Textile and Apparel Industries In Indonesia - Sari Sari; Bambang Eko Afiatno (Trunojoyo University of Madura, 2022)
The Covid-19 pandemic has disrupted all sectors of life, including the economy. One of the the sectors most negatively affected by the Covid-19 pandemic in Indonesia is textile and apparel industry. This study investigates Indonesian textile and apparel export volumes, exchange rate of rupiah to us dollar and covid-19 as a dummy variable on the export performance of textile and apparel industry. This study used data from Statistics Indonesia, the World Trade Organization and the Federal Reserve Bank for January 2019 to December 2020 and analyzed by using time series forecasting with multiple linear regression. The export performance of textiles and apparel is proxied by total export of Indonesian textiles and apparel. The result of this study indicates that performance of Indonesian textile and apparel exports during the covid-19 outbreak in Indonesia decreased by 11.04% compared to normal conditions. Instead of being affected by the pandemic in the country, the pandemic that occurred in export destination countries could also reduce the value of Indonesia's textile and apparel exports, with the highest declines occurring in the USA (23.85%). Government can start by reducing the requirements for export destinations to America to recover the value of textile and apparel exports. In addition, the government can also reduce the burden on textile and apparel companies during the pandemic.